Hippocampal morphological atrophy and distinct patterns of structural covariance network in Alzheimer’s disease and mild cognitive impairment - Miao, Dawei; Zhou, Xiaoguang; Wu, Xiaoyuan; Chen, Chengdong; Tian, Le (Frontiers in Psychology, 2022)
Elucidating distinct morphological atrophy patterns of Alzheimer’s disease (AD) and its prodromal stage, namely mild cognitive impairment (MCI) helps to improve early diagnosis and medical intervention of AD. On that account, we aimed to obtain distinct patterns of voxel-wise morphological atrophy and its further perturbation on structural covariance network in AD and MCI compared with healthy controls (HCs). T1-weighted anatomical images of matched AD, MCI and HCs were included in this study. Gray matter volume was obtained using voxel-based morphometry and compared among three groups. In addition, structural covariance network of identified brain regions exhibiting morphological difference was constructed and compared between pairs of three groups. Thus, AD patients have a reduced hippocampal volume and an increased rate of atrophy compared with MCI and HCs. MCI exhibited a decreased trend in bilateral hippocampal volume compared with HCs and accelerated right hippocampal atrophy rate than HCs. In AD, the hippocampus further exhibited increased structural covariance connected to reward related brain regions including anterior cingulate cortex, putamen, caudate and insula compared with HCs. In addition, patients with AD exhibited increased structural covariance of left hippocampus with the bilateral insula, inferior frontal gyrus, superior temporal gyrus and cerebellum than MCI. These results reveal distinct patterns of morphological atrophy in AD and MCI, providing new insights into pathology of AD.